CaMKII is a modulator in neurodegenerative diseases and mediates the effect of androgen on synaptic protein PSD95 - Mi, Shixiong; Chen, Huan; Lin, Peijing; Kang, Peiyuan; Qiao, Dan; Zhang, Bohan; Wang, Zhao; Zhang, Jingbao; Hu, Xiangting; Wang, Chang; Cui, Huixian; Li, Sha (Frontiers in Genetics, 2022)
Androgens rapidly regulate synaptic plasticity in hippocampal neurones, but the underlying genomic and non-genomic mechanisms remain unclear. In this study, we carried out a comprehensive bioinformatics analysis of functional similarities between androgen receptor (AR) and the synaptic protein protein postsynaptic density 95 (PSD95) to evaluate the genomic effect. Using different measurements and thresholds, we obtained consistent results illustrating that the two proteins were significantly involved in similar pathways. We further identified CAMKII plays a critical role in mediating the rapid effect of androgen and promoting the expression of the PSD95. We used mouse hippocampal neurone HT22 cells as a cell model to investigate the effect of testosterone (T) on intracellular Ca2+ levels and the mechanism. Calcium imaging experiments showed that intracellular Ca2+ increased to a peak due to calcium influx in the extracellular fluid through L-type and N-type voltage-gated calcium channels when HT22 cells were treated with 100 nM T for 20 min. Subsequently, we investigated whether the Ca2+/CaMKII signalling pathway mediates the rapid effect of T, promoting the expression of the synaptic protein postsynaptic density 95 (PSD95). Immunofluorescence cytochemical staining and Western blotting results showed that T promoted CaMKII phosphorylation by rapidly increasing extracellular Ca2+ influx, thus increasing PSD95 expression. This study demonstrated that CaMKII acts as a mediator assisting androgen regulate synaptic protein PSD95 from both genomic and non-genomic perspective. Also, it provides evidence for the neuroprotective mechanisms of androgens in synaptic plasticity and reveals the gated and pharmacological mechanisms of Ca2+ channel family members for androgen replacement therapy.